Streetscape character and parking behavior analysis towards efficient parking structure considerations in Davao City central business district - Alcantara, Desiree Gwenn L.; Malaque, Isidoro R. III (2023)
On-street and illegal parking are both common in Davao City's Central Business Districts. Employees frequently leave their vehicles parked, leaving customers no option but to quickly park illegally or off-street. The prolonged cruising time, traffic from road freight, and inefficient impacts would all result from this conduct. Weak enforcement of policies would increase demand for parking and circulation places. This study, therefore, presents streetscape human perception model of streets within Poblacion District displaying relationship how it impacts the parking behavior. Parking configuration was assessed through image segmentation and direct observation. Using AutoCAD in image segmentation acquired results of Imageability, Liability, Openness, and Greenness having the highest to lowest significance based on human perception. Survey questionnaires and relationship to the built environment were assessed through multiple correlation acquiring significant relationship between Openness and Security (Magsaysay Avenue). Factors such as Liability, Openness, Greenness, and Imageability have no effect on the parker's parking preference indices of Proximity, Comfortability, Security, and Availability in the remaining study areas (City Hall Drive and Sta. Ana Avenue). With this, a destination station is envisioned to be proposed in the chosen site. This is where there are high volumes of pedestrian footfall, shopping facilities are likely to be catered and succeed. Upon its provision, both parking behavior, and streetscape character indices are to be resolved.
Thesis (BS Architecture)--University of the Philippines Mindanao,2023